Molecular analysis of bacterial communities in marbled spinefoot (Siganus rivulatus) and squaretail coral grouper (Plectropomus areolatus), in Jeddah, Saudi Arabia - Hassan A.I. Ramadan; Mamdouh T. Jamal; Hany M. El-Wahsh; Mohamed Abu El-Regal (Egyptian Journal of Aquatic Research)
Microbial communities inhabiting the external and internal organs of fish play crucial roles both in the animals and their environment. Understanding the microbial diversity and composition in fish is essential for assessing their health status, potential zoonotic risks, and the impact of environmental factors. This study aimed to investigate the bacterial flora associated with two commercially significant fish species, Siganus rivulatus (marbled spinefoot) and Plectropomus areolatus (coral trout), harvested from the Jeddah Local Market, Kingdom of Saudi Arabia. Four sample types (skin, tissue, intestines, and gills) were collected from each species to characterize the diversity and abundance of the bacterial communities. Molecular analysis was performed using 16S rRNA gene sequencing, which is a powerful tool for identifying bacterial species at the taxonomic level. The results showed that bacterial genera identified in the samples were Priestia, Marinobacter, Vibrio, Staphylococcus, Metabacillus, Niallia, Idiomarina, and Vreelandella. The results revealed distinct microbial profiles between the two species and across different anatomical sites with notable variations in microbial richness and composition. These findings contribute to the growing body of knowledge on the microbiological landscape of marine organisms and underscore the need for regular monitoring of bacterial contamination to ensure seafood safety.